HUBUNGAN KADAR OVERNIGHT MONEY ANTARA BANK KONVENSIONAL DENGAN BANK ISLAM: BUKTI EMPIRIKAL DI MALAYSIA - Karim, Zulkefly Abdul; Asri, Norain Mod; Wajdi, M. Farid; Antoni, Antoni (Universitas Muhammadiyah Surakarta, 2006)
The objective of this study is to examine the relationship between overnight money of Islamic bankand conventional bank based on daily data begins from 12th October 1998 until 10th June 2005.This study is important to determine whether overnight money of conventional bank or overnight moneyof Islamic bank, become the leader or follower in the interbank money market. The econometrics testssuch as unit root test, VAR model and Granger causality test have been applied. Result shows thatboth variables are stationary at level form or I(0). This implies that we donât need to further analysiswith cointegration test. In this case, we appllied the traditional model of VAR and Granger causalitytest. Empirical findings indicates that the existence of bi-directional causality between overnight moneyof Islamic bank and conventional bank.